Market size and vertical structure in the rail way industry - Noriaki Matsushima; Fumitoshi Mizutani (Osaka University, Institute of Social and Economic Research (ISER), 2011)
We provide a theoretical framework to discuss the relation between market size and vertical structure in the railway industry. The framework is based on a simple downstream monopoly model with two input suppliers, labor forces and the rail infrastructure firm. The operation of the downstream firm (i.e., the train operating firm) generates costs on the rail infrastructure firm. We show that the downstream firm with a larger market size is more likely to integrate with the rail infrastructure firm. This is consistent with the phenomenon in the railway industry.
Keywords: L22; L13; R32; 330; vertical integration; railway industry; market size; vertical coordination; Vertikale Integration; Marktgröße; Eisenbahngesellschaft; Schienenstrecke; Transportkosten; Monopol